Effects of hole taper on high speed steel workpiece using EDM injection flushing - M. S., Reza; Nor Farhanah; S. H., Tomadi; M. A., Hassan; W. S. W., Harun; M. A., Azmir; Z., Hamedon (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.